Adenomatous hyperplasia of the minor salivary glands presenting as “tongue bump:” A rare case report (Indian Journal of Case Reports, 2021)
The tongue remains the most common intraoral site for oral cancer worldwide, and in several countries, it is still considered a serious public health problem. Any lesion presenting as swelling on the tongue can mimic malignancy on clinical grounds and conclusive opinion requires histopathological examination. Adenomatoid hyperplasia of minor salivary glands is a rare hyperplastic oral lesion that can present anywhere in the oral cavity as an asymptomatic mass or nodule. It mainly involves soft and hard palate but its occurrence in the tongue is very rare with only one case cited in the literature. Here, we report the case of adenomatous hyperplasia of minor salivary glands in a 55-year-old female. The purpose of this case report is to highlight one such case which presented as a nodule on the tongue to make the clinicians and dentists aware of this unusual entity, as at this location, it becomes highly significant to distinguish adenomatous hyperplasia of minor salivary glands from relatively common epithelial and salivary gland neoplasms.